Implications Implikasi Putusan MK No.135/PUU-XXII/2024 terhadap keserentakan pemilu nasional - salsabila, diva kurnia dwi (Maliki Interdisciplinary Journal, 2026)
Constitutional Court Decision No. 135/PUU-XXII/2024 marks a significant shift in the design of electoral simultaneity in Indonesia. The decision affirms that national elections and regional head elections can no longer be held simultaneously, but must instead be separated in order to align with the principles of effective administration, legal certainty, and the protection of citizens’ political rights. This change emerged in response to the complexity of the 2019 simultaneous elections, which resulted in excessive workloads for election administrators, a high potential for administrative errors, and a decline in the quality of voter participation. This article aims to comprehensively examine the juridical and practical implications of the decision for the architecture of national electoral simultaneity. Employing normative legal research methods through statutory, conceptual, and judicial decision approaches, the study analyzes how the legal construction embodied in Constitutional Court Decision No. 135 reshapes the regulation of electoral simultaneity under the Election Law. The findings indicate that separating national elections from regional elections gives rise to three main implications. First, there is a repositioning of the norm of simultaneity that necessitates adjustments to the constitutional calendar, particularly with regard to the nomination stages and the terms of office of public officials. Second, such separation creates opportunities to improve the quality of election administration, as the focus and workload of election organizers become more proportionate. Third, this change affects national and local political configurations, since the cycles of political legitimacy at the central and regional levels no longer operate concurrently. The study concludes that Constitutional Court Decision No. 135 not only addresses technical issues of election administration, but also provides a new direction for a more systematic and sustainable model of Indonesia’s electoral democratic governance.